DIVERSIFICATION OF THE SOCIO-ECONOMIC SECTORS FOR THE PERIOD 2010 – 2023 IN THE RURAL MUNICIPALITIES OF THE SOUTH CENTRAL REGION (TRAKIA JOURNAL OF SCIENCES, 2025)
In the modern world of globalization and introduction of new technological processes, the diversification in rural areas (RA) of Bulgaria appears as an inevitable process, in the "replacement" of basic sectors with new approaches in the socio-economic environment. The purpose of the scientific development is to attempt to analyze a part of the sectors according to the Classification of Economic Activities - 2008, located in the RA of the South-Central Region (SCR) for the period 2010 - 2023. In the study have been applied the methodology related to the analysis of labor efficiency (coefficient) and a comparative analysis based on the sectors diversification in relation to employed persons and non-financial enterprises for the period 2010-2023. The location of RA in the SCR has a key role for the localization and development of a part of the socio-economic sectors responding to the new modern needs.